FOSTERING ATTITUDES OF RELIGIOUS MODERATION IN STUDENTS THROUGH MULTICULTURAL COUNSELING - NELLY MARHAYATI; PASMAH CHANDRA (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2023)
The purpose of this article is to complement previous studies that have discussed multicultural counseling. Where previous studies discussed fostering an inclusive religious attitude through multicultural counseling and there was also a discussion about multicultural counseling to prevent terrorist behavior. Referring to the previous two studies, in this paper, researchers try to understand the views of Islamic guidance and counseling students, about multicultural counseling in order to analyze religious moderation attitudes in students as prospective Muslim counselors. This study collected empirical data through open-ended questions with g-form assistance from 14 final semester students of the BKI study program of UIN Fatmawati Sukarno Bengkulu. Based on the informant's answer, it was found that the attitude toward religious moderation has grown in students, this is seen from the answers of informants who accept differences and consider differences to be common, unique, interesting, and a challenge for a Muslim counselor and they will still accept clients who have different backgrounds both religious, racial and cultural even if they have the status of a Muslim counselor in the future. The weakness of this study has not been found to be an answer to what kind of counseling strategies will be carried out in dealing with clients who have different backgrounds with counselors. Through this research, it is hoped that it will contribute to the scientific development of Islamic Counseling Guidance, especially in developing multicultural counseling as a means to instill an attitude of religious moderation in society.